Comparison of breakthrough Gram‐positive cocci infection during vancomycin vs teicoplanin therapy in patients receiving haematopoietic stem cell transplantation. (13th July 2020) - Ohata, Koichi; Kitagawa, Junichi; Niwa, Takashi; Takahashi‐Yamauchi, Tomoyo; Harada, Saki; Matsumoto, Takuro; Nakamura, Nobuhiko; Nakamura, Hiroshi; Kanemura, Nobuhiro; Shimizu, Masahito; Suzuki, Akio
Abstract: What is Known and Objective: Our previous report indicated that teicoplanin (TEIC) caused fewer adverse effects than vancomycin (VCM) in patients with febrile neutropenia (FN) receiving haematopoietic stem cell transplantation (HSCT). However, we observed breakthrough methicillin‐resistant‐ Staphylococcus haemolyticus (MR‐S haemolyticus ) infection during TEIC therapy in these patients. In this study, we sought to compare the incidence of breakthrough Gram‐positive cocci (GPC) infection during VCM and TEIC therapy in this population. Methods: A single‐centre, retrospective cohort study was conducted. Patients who had received HSCT and were administered VCM (n = 19) or TEIC (n = 38) for FN from 1 September 2011 to 31 August 2019 were enrolled. We compared the incidence of breakthrough GPC infection between the VCM and TEIC groups. Results: Breakthrough GPC infection during glycopeptide therapy in febrile neutropenic patients received HSCT was observed in three patients (7.9%) in the TEIC group but in none of patients (0%) in the VCM group. MR‐S haemolyticus with low glycopeptide susceptibility (TEIC MIC = 2‐8 μg/mL, VCM MIC = 2‐4 μg/mL) was isolated from blood cultures in all patients with breakthrough GPC infections. All breakthrough infections were cured by changing from TEIC to daptomycin (DAP). What is New and Conclusion: The incidence of breakthrough GPC infection during glycopeptide therapy in febrile neutropenic HSCT patients was higher in the TEIC group than in the VCM group. MR‐S haemolyticus with low glycopeptide susceptibility was isolated from all patients with breakthrough GPC infection and successfully treated with DAP. Abstract : The incidence of breakthrough Gram‐positive cocci infection during glycopeptide therapy in febrile neutropenic patients who received hematopoietic stem cell transplantation was higher, albeit without significance, in the teicoplanin group than in the vancomycin group (7.9% vs 0%, P  = .544).